CASE STUDY OF MUSIC ARTS LEARNING AMONG STUDENTS AT SMP NEGERI 2 PALEMBANG: ANALYSIS OF THE LEARNING PROCESS AND LEARNING OUTCOMES - Dedy Firmansyah Fadhillah Hidayatullah (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Music arts learning in schools plays an important role in developing students’ creativity, musical skills, and appreciation of cultural arts. One of the traditional musical instruments used in music learning activities is the angklung. This study aimed to describe the process of angklung music learning among eighth-grade students at SMP Negeri 2 Palembang, including the planning, implementation, and evaluation stages, as well as the factors influencing the learning process. This study used a qualitative approach with a descriptive case study method. Data collection techniques consisted of observation, interviews, and documentation. The research subjects included a music teacher and 31 students of class VIII.7. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that angklung music learning was implemented through three stages: planning, implementation, and evaluation. During the implementation stage, learning activities emphasized group practice in playing angklung, enabling students to improve their musical performance skills, teamwork, and learning interest in music arts. Although there were limitations in musical instrument facilities and infrastructure, the teacher was able to manage the learning process effectively so that practical activities could still run well. Furthermore, angklung learning activities increased student participation and fostered appreciation of traditional music.